The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1080/21645515.2019.1586040
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of the RTS,S/AS01 malaria vaccine in infants and children: additional data from a phase III randomized controlled trial in sub-Saharan Africa

Abstract: A phase III, double-blind, randomized, controlled trial (NCT00866619) in sub-Saharan Africa showed RTS,S/AS01 vaccine efficacy against malaria. We now present in-depth safety results from this study. 8922 children (enrolled at 5–17 months) and 6537 infants (enrolled at 6–12 weeks) were 1:1:1-randomized to receive 4 doses of RTS,S/AS01 (R3R) or non-malaria control vaccine (C3C), or 3 RTS,S/AS01 doses plus control (R3C). Aggregate safety data were reviewed by a multi-functional team. Severe malaria with Blantyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 42 publications
1
42
1
Order By: Relevance
“…Evidence from settings with very good access to antimalarial treatment are consistent with our findings. In a malaria vaccine (RTS,S) trial setting, with clinical care being part of the trial design, the ratio of the proportion of SMA versus CM amongst severe cases in 5-to 7-monthold children was lower than that observed in our data for the same age group (SMA versus CM: 5.0 for RTS,S trial and 9.0 for our pooled data set) [69]. This may suggest SMA cases are more amenable to prevention by treatment than CM cases.…”
Section: Discussioncontrasting
confidence: 83%
“…Evidence from settings with very good access to antimalarial treatment are consistent with our findings. In a malaria vaccine (RTS,S) trial setting, with clinical care being part of the trial design, the ratio of the proportion of SMA versus CM amongst severe cases in 5-to 7-monthold children was lower than that observed in our data for the same age group (SMA versus CM: 5.0 for RTS,S trial and 9.0 for our pooled data set) [69]. This may suggest SMA cases are more amenable to prevention by treatment than CM cases.…”
Section: Discussioncontrasting
confidence: 83%
“…This is explained by the fact that any rare complication is less likely to occur when the group of subjects is small. continuous monitoring is important in case of complications that occur with delayed effect (40). during a pandemic, these sequential studies may be shortened and partially overlapped, but it is important that thousands of vaccinated people are followed for several months before the general purpose vaccine is approved.…”
Section: Vaccines: An Overviewmentioning
confidence: 99%
“…A WHO-commissioned systematic review provided more equivocal evidence, concluding that receipt of DTP was associated with a possible increase in all-cause mortality on average (relative risk 1.38, 95% CI 0.92-2.08), with the effect seeming stronger in girls than in boys [12]. The safety profile of the RTS,S/AS01 malaria vaccine in infants and children in sub-Saharan Africa also showed that the effect of vaccination on all-cause mortality was substantially modified by sex, with higher all-cause mortality in girls but not in boys [14,15]. These observations have led some scientists to propose that nonlive vaccines-despite providing specific protection against targeted diseases-may have detrimental nonspecific effects (NSEs) on overall morbidity and mortality rates in recipients in high-mortality populations, and that these effects are more pronounced in females [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This topic remains controversial [11], as much of the evidence is from studies with high risk of bias conducted in a limited range of settings [12,13]. The RTS,S/AS01 malaria vaccine-another nonlive vaccine-is also associated with higher all-cause mortality in female but not male children [14,15]. More generally, both safety and immunogenicity of vaccines are shown to be influenced by sex [16][17][18][19], and greater consideration must be given to sex as a biological variable in vaccine studies.…”
Section: Introductionmentioning
confidence: 99%